Pengaruh Tata Kelola Perusahaan Terhadap Earning Per Share - Intan Oktavia; Yanuar Ramadhan (MES Management Journal, 2026)
This study aims to analyze the relationship between corporate governance and earning per share, which uses five independent variables, Managerial Ownership (MO), Audit Committee (AC), Institutional Ownership (IO) Board of Commissioners Size (BOS), Independent Commissioner (1C), and Earning Per Share (EPS) as the dependent variabel. This research data is secondary, with thepopulation obtained, 47 companies in the banking sector on the Indonesia Stock Exchange (IDX). Then, of the 47 companies, there were 17 that fot the criteria, so there were 51 samples in the 2021-2023 period purposie sampling techniqe. This tes method, Quantitative and as a test usiNg Multiple Linear Regression, and using a statistical test application. The result obtained by ManagerialOwnership on increasing Earning Per Share have a negative effect, the Audit Committee has no effecton increasing Earning Per Share, Institutional Ownership on increasing Earning Per Share has anegative effect, Board of Commissioners Size also has no effect on increasing Earning Per Share, and the presence of Independet Commissioners makes a positive contibution to increaisng EarningPer Share. This research can also be useful and be considered by inestors as an initial analysis before investing their capial. For companies, they must build and effective governance system, and improve operational performance so that thecompany can achieveits goals.